2022
DOI: 10.1108/jpbm-05-2021-3500
|View full text |Cite
|
Sign up to set email alerts
|

How isolation leads to purchasing luxury brands: the moderating effects of COVID-19 anxiety and social capital

Abstract: Purpose The purpose of this paper is to investigate how consumers’ luxury purchase behavior has been affected by COVID-19. A theoretical framework is proposed to determine how isolation leads to intention to purchase luxury brands through bandwagon luxury consumption behavior. Additionally, the moderating effects of COVID-19 anxiety and social capital on the relationship between bandwagon luxury consumption behavior and subjective well-being and intention to purchase luxury brands are tested. Design/methodol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
20
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(23 citation statements)
references
References 158 publications
(180 reference statements)
2
20
1
Order By: Relevance
“…As an escape mechanism, individuals limit their exposure to noxious stimuli during stressful situations by disengaging themselves from them and diverting their attention to wishful thinking and fantasies (Tobin et al , 1989). To escape, people may also turn to close others (Thapa et al , 2022). Research indicates that seeking social support helps individuals more effectively with long-term health benefits and psychological well-being (Gurung et al , 1997; Malik and Paswan, 2022; Pierce et al , 1996).…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…As an escape mechanism, individuals limit their exposure to noxious stimuli during stressful situations by disengaging themselves from them and diverting their attention to wishful thinking and fantasies (Tobin et al , 1989). To escape, people may also turn to close others (Thapa et al , 2022). Research indicates that seeking social support helps individuals more effectively with long-term health benefits and psychological well-being (Gurung et al , 1997; Malik and Paswan, 2022; Pierce et al , 1996).…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…Phygital enables them to develop, maintain and strengthen relationships with existing friends, meet new people and make new connections/friends from other social groups. Prior studies have suggested that phygital connectedness comprises interaction with friends and peers (representing closer connectedness), opinion leaders, influencers and celebrities (representing social connectedness) (Sun et al, 2022) in order to generate emotional bonds, support and happiness during a stressful time (Thapa et al, 2022). This study adds phygital-facilitating engagement with virtual human/animal companions, work from home, study from home and entertainment at home amidst the pandemic.…”
Section: Discussionmentioning
confidence: 96%
“…Prior studies have suggested that phygital connectedness comprises interaction with friends and peers (representing closer connectedness), opinion leaders, influencers and celebrities (representing social connectedness) (Sun et al. , 2022) in order to generate emotional bonds, support and happiness during a stressful time (Thapa et al. , 2022).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations